49th Winter School on Wave and Quantum Acoustics XLVIIIth Winter School on Environmental Acoustics and Vibroacoustics Szczyrk, Poland, February 24–27, 2020 - Dariusz Bismor (Archives of Acoustics, 2020)
49th Winter School on Wave and Quantum Acoustics constituted platforms for sharing the results and achievements obtained in different branches of physical acoustics, as molecular acoustics, quantum acoustics, acousto-optics, magnetoacoustics, photoacoustics, acoustics of solid state, acoustic emission, and others. Moreover, researches in some selected topics related to those mentioned above (e.g. optoelectronics, relaxation processes) were presented during the school.